Legal plurality: an analysis of power interplay in Mekong hydropower - Suhardiman, Diana; Giordano, Mark (Informa UK Limited, 2014)
The changing notion of state territoriality highlights overlapping power structures at international, national, and local scales and reveals how states can be “differently” powerful. This article analyzes how the interplay of these power structures shapes the dynamics of natural resource management in one of the world’s fastest changing transboundary basins, the Mekong. Taking the Lao People’s Democratic Republic as a case study, we highlight the existing inconsistency and institutional discrepancies in land, water, and environmental policy related to hydropower and illustrate how they are manifested in multiple decision-making frameworks and overlapping legal orders. The resulting legal plurality reveals the inherently contested terrain of hydropower but, more important, it illustrates how the central state has been able to use contradictory mandates and interests to further its goals. The specific Mekong hydropower case demonstrates that an understanding of power geometries and scale dynamics is crucial to meaningful application of social and environmental safeguards for sustainable dam development.More broadly, the case sheds light on the important role of states’ various agents and their multiple connections, partially explaining how the achievement of the central state’s goals can be derived from legal plurality rather than hindered by it.